144 Smoking adjusted incidence of bladder cancer using proxy smoking from lung cancer in nordic males. (24th April 2018) - Hadkhale, Kishor; Martinsen, Jan Iver; Weiderpass, Elisabete; Kjaerheim, Kristina; Lynge, Elsebeth; Sparen, Pär; Tryggvadottir, Laufey; Pukkala, Eero
Abstract : Objectives: The objective of this study was to observe the occupational variation in risk of bladder cancer that is not attributable to smoking. Methods: In the Nordic Occupational Cancer study (NOCCA), 1 11 458 cases of bladder cancer and 2 08 297 cases of lung cancer cases were observed among men in Denmark, Finland, Iceland, Norway and Sweden during 1961–2005. The expected numbers of bladder cancer in occupational category were corrected with smoking prevalence estimated on the basis of lung cancer risk in the category. Crude and smoking-adjusted standardised incidence ratios (SIR) with 95% confidence intervals (CI) were calculated for each occupation. Results: The smoking-adjusted SIR for most of the occupations was closer to 1.00 than the unadjusted SIR. It signifies the role of smoking as a risk factor of both bladder and lung cancers. Highest statistically significant smoking-adjusted SIRs were observed among chimney sweeps (SIR 1.33, 95% CI: 1.08 to 1.61), waiters (1.18, 1.04–1.34) hairdressers (1.16, 1.04–1.28), cooks and stewards (1.13, 1.01–1.27) and printers (1.10, 1.03–1.06). Conclusion: Smoking is a strong risk factor bladder cancer but there are other factors in some specific occupations in addition to smoking. The occupational variation in risk of bladder cancer is small when adjusted for smoking.